Perfluoroalkylation reactions of (hetero)arenes - Baraja Vallejo, Sebastian (2015)
Perfluoroalkylation reactions of arenes have not been the subject of intense study as has been the case for the trifluoromethylation reactions of aromatics. However, the new synthetic methods proposed for achieving homolytic aromatic substitution reactions with perfluoroalkyl moieties have begun to claim a relevant role in functionalization reactions, as revealed by the interesting properties of arenes with large perfluoroalkyl chains. Methods for achieving Ar–Rf bonding reactions can be classified into thermal and photochemical, which can in turn make use of transition metals or be non-metal catalyzed. Reactions are mainly radical in nature. Radical methods for introducing Rf moieties into arenes have resulted as being the most popular and versatile options available to synthetic chemists.